2007
DOI: 10.1080/09540120701203931
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing and disclosure: a qualitative analysis of TB patients in South Africa

Abstract: In South Africa, more than 60% of TB patients have HIV co-infection. Voluntary counseling and testing (VCT) is critical to effective HIV prevention, and TB facilities are optimal venues for delivery of these services. This study employed qualitative research methods to explore the decision-making processes for HIV testing and serostatus disclosure by 21 patients hospitalized with multi/extensively-drug resistant TB (M/XDR-TB) in Durban, KwaZulu Natal. Data collected from in-depth interviews characterized 3 bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 20 publications
6
73
1
6
Order By: Relevance
“…Overall WHO estimation for HIV prevalence in new diagnosed TB patients worldwide is 8% (8). Regardless of IDU cases, HIV prevalence rate in the current study was similar to other studies reported by Zhou et (17)(18)(19)(20)(21). Reported HIV prevalence rate (17-21) ranges from 2.27% (Iran) and 2.3% (China) to 44% (Tanzania) and 60% (South Africa).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall WHO estimation for HIV prevalence in new diagnosed TB patients worldwide is 8% (8). Regardless of IDU cases, HIV prevalence rate in the current study was similar to other studies reported by Zhou et (17)(18)(19)(20)(21). Reported HIV prevalence rate (17-21) ranges from 2.27% (Iran) and 2.3% (China) to 44% (Tanzania) and 60% (South Africa).…”
Section: Discussionsupporting
confidence: 91%
“…population based or hospital based study) and behaviors of the subjects under study(e.g. IDUs or unsafe sex contacts) (17)(18)(19)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm earlier studies showing that sociocultural determinants such as gender (being female), the status of married woman and occupation reported as housewife have been associated with diagnostic delays [22,23]. Husbands may become upset when their wives are asked to undergo testing for HIV, since it is associated with immoral behavior [24]. Similarly to our study findings, other studies have reported that female patients tend to receive less support from their families and often face financial, physical and social barriers in accessing health services [25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Socio-economic challenges may also decrease the likelihood of HIV testing, due to lack of financial resources that would enable individuals to have access to health care services. [18][19][20][21] The effect of HIV/AIDS factors (e.g., stigma and discrimination, risk perception of HIV infection, risky behaviour, HIV awareness, or knowing someone who died of HIV/AIDS) on HIV testing may depend on an individual's predisposing factors such as age, education, marital status, social and economic status. 5,22 These interactions may lead to an increased risk perception of HIV infection which may in turn decrease the willingness to utilise health care services that are linked to HIV.…”
Section: Introductionmentioning
confidence: 99%
“…12,19,29 All of these may lead to an increased risk perception of HIV infection, leading to lower or higher uptake of HIV testing. In line with the effects of risk perception on healthcare utilisation, studies have shown that perceived susceptibility as a result of risky sexual behaviour exacerbates risk perception of HIV infection, in turn leading to underutilisation of health care services.…”
Section: Introductionmentioning
confidence: 99%